Necessity and challenges of nature conservation - Mohd Kamil, Nor Amani Filzah; Cheah, Wing Hong; Abdul Kadir, Aeslina; Hashim, Nor Haslina; Chin, Ming Wei; Mizad, Meizareena (Penerbit UTHM, 2020)
Nature conservation is the preservation of resources that are produced naturally for example wild animals and plants, ecosystem and biodiversity especially from the effects of human activities for example exploitation and industrialization. Nature conservation is necessary in protecting the biodiversity for example to prevent animal species from endangering or extinct, protection for natural ecosystem and human’s freshwater sources for drinking purposes. Moreover, nature conservation is important in maintaining a long-life natural environment as well as an environment that is sustainable towards development. However, nature conservation is not an easy task as it requires a lot of manpower as well as money. Therefore, nature conservation is challenging as well. The challenges of nature conservation include human’s overpopulation, global warming and overharvesting. Human’s overpopulation is one of the most challenging factors that influences the practice of nature conservation.